2017
DOI: 10.11648/j.ja.20170506.11
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Involvement in Decision Making: Episiotomy Procedure

Abstract: Abstract:Background: Involving patient in decision making for their care can enhance satisfaction and promote health outcomes in particular in the nursing fields. As The World Health Organization Principles of Perinatal Care has recommended that care should involve women in decision making. This principle strongly endorses for improving effective perinatal care. Decision making regard to treatment options is a concept that has increased widespread appeals to healthcare providers and users in recent year. Evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The decision of performing the procedure was made mostly by their health care provider, a similar situation is also observed in other studies. 17 Episiotomy being one of the most frequent surgical interventions, still is overlooked and does not fulfil the steps and measures as any other surgical manipulation. 18 As seen in our study, women should be informed about the procedure, its risks and possible outcomes, and have the option to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%
“…The decision of performing the procedure was made mostly by their health care provider, a similar situation is also observed in other studies. 17 Episiotomy being one of the most frequent surgical interventions, still is overlooked and does not fulfil the steps and measures as any other surgical manipulation. 18 As seen in our study, women should be informed about the procedure, its risks and possible outcomes, and have the option to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al reported that antenatal education about episiotomy helped comfort women about the process of giving birth and increased the level of acceptance of the procedure when indicated [1] . Patients’ understanding and involvement in decision-making have proven to raise satisfactory levels and quality of care [13] . It is now the role of physicians to weigh the risks and benefits of episiotomy and individualize each experience of birth.…”
Section: Introductionmentioning
confidence: 99%
“…Patients’ involvement in the process of decision-making had proven to raise satisfactory levels and quality of care [13] . Edwin et al had advocated to adopt a patient-oriented approach to improve patients understanding [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the twenty first century, the practice of routine episiotomy by midwives and obstetricians have remained under public scrutiny 14 . The alignment of the clinicians reasons for episiotomy with maternal preference for episiotomy have generated discourse among researchers and clinicians globally 15 . Consequently, a study of this nature which is aimed at examining the perspectives of skilled birth attendants and pregnant women regarding episiotomy in health facilities within Africa is justified.…”
Section: Introductionmentioning
confidence: 99%